A.F. Nessler’s Moscow German-Russian Dictionary as a source for studying German military lexis of the 1920s. A pilot study - Sobczak, Michał (Papers in Linguistics, 2025)
This article addresses the little-studied problem of German military lexis of the interwar period. The linguistic source for the analysis is the Moscow German-Russian Dictionary by A.F. Nessler, published in 1928. The military lexical items excerpted from the source (entries for letters A-B) were compared with the headword grid of the Berlin Military Dictionary, published in the same year by Offene Worte. As a result of the undertaken analysis, based on the DWDS dictionary and text databases, it was determined which of the collected lexemes (and with what frequency) occurred in German before 1928. The aim of the research was to determine whether such a unique general dictionary is a valuable source for the study of German military vocabulary of the interwar period. Considering the results of the analyses, which proved that Nessler’s compilation contains rare military lexicon (including agnonyms), it was concluded that its further scrutiny is justified and promising.